Impact of Comorbidities on Local Anesthetic Hypersensitivity: A Decade of Clinical Experience - Kılınç, Mehmet; Çölkesen, Fatih; Sadi Aykan, Filiz; Evcen, Recep; Önalan, Tuğba; Akkuş, Fatma Arzu; Yıldız, Eray; Arslan, Şevket (The European Research Journal, 2026)
Objectives: Clinicians widely utilize local anesthetic (LA) agents in pain management and surgical interventions. Nevertheless, drug hypersensitivity reaction (HR) to their use continue to raise considerable concern among both clinicians and patients. The present study aims to investigate the relationship between local anesthetic hypersensitivity reactions (LA-HRs) and comorbid conditions in patients referred to our clinic. Methods: Clinical data and test results of patients who were referred to our allergy clinic for evaluation of suspected LA-HR were retrospectively reviewed. Skin tests (ST) and subcutaneous provocation tests (SPT) were performed. Results: A total of 200 patients were included in the study. The most common reason for referral was a suspected LA-HR (80%), followed by a history of HR to other drugs with a need for LA use during upcoming procedures (20%). Among 160 patients with suspected LA- HR, only 5.6% demonstrated confirmed hypersensitivity by positive ST and SPT. Of the 40 patients with a history of HR to other drugs, only 2.5% tested positive for LA-HR. A history of comorbidity was present in 70% patients. Patients with suspected LA-HR had a significantly higher prevalence of comorbidities compared to those with HR to other drugs. However, none of the patients who tested positive had a history of comorbidity. Conclusions: Confirmed hypersensitivity risk among patients reporting LA-HR is very low. Although comorbidities were more common among patients reporting LA-HR, none of the patients with confirmed allergy had any comorbidities, underscoring the low confirmed hypersensitivity rate in this population.